Poetry and Peace: Explorations of Language and “Unlanguage” as Transformative Pedagogy (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
Poetry makes us human. Without poetry and other art forms, the survival of global, planetary consciousness and, indeed, our very existence as a species is called into question. Poetry, through words, reduces our experiences to their essence and, at the same time, uplifts our souls to their highest. The poet and peace activist Denise Levertov (1923-1997) wrote that poets, more than any others, “recognize language as a form of life and a common resource to be cherished and served as we should serve and cherish earth and its waters, animal and vegetable life, and each other.” Levertov believed that the poet’s task is to hold in trust that knowledge that language is considered power (my italics). Quoting Ibsen, Levertov noted that the task of thepoet is to  “make clear to himself [sic], and thereby to others, the temporal and eternal questions which are astir in the age and community to which he belongs.”